A place for all? A qualitative study exploring how legacies of exclusion impact library engagement - Saunders, Michaela R. (My University, 2025)
This community-engaged qualitative study explored a knowledge gap in understanding about how the past – specifically a history of de facto segregation within community spaces – has shaped current reality of public library utilization in the state capital micro-urban city of Topeka, Kansas. Interviewing patrons of library-partnered organizations in the geographic area of a potential future library branch allowed them to share lived-experience narratives of past and current library use and reveals their needs and hopes. These experiences and opinions can aid library leaders in their decision-making. Social infrastructure in the United States was designed by white people to serve white people. In the specific context of public libraries, which were established to advance self-help and civic participation, almost no scholarly attention has been given to the ways that past exclusions influence how Black, Indigenous, and other people of color think about, experience, and use these spaces and their services. Thus, the most basic questions of how library leaders might redress continued inequities and inequality remain unconsidered. Such work is required, through leadership action. Until society – and social infrastructure leaders in particular –intentionally recognize and support cultural norms beyond those of structural whiteness, exclusion will continue. Therefore, I sought to understand the lived experiences of library patrons, letting their stories of library engagement speak for how they think, and feel, about their library experiences. My study sought to investigate, specifically: RQ1: Why do residents choose to engage or not with their local public library? RQ2: In what ways do historical legacies of exclusion impact these choices? I found, in the context of the Topeka & Shawnee County Public Library (TSCPL), minoritized patrons interviewed do not feel overtly excluded by or in the library. The findings of this research nevertheless demonstrate psychological and geographic relationality are key to feelings of comfort and ease within the library, and both willingness and ability to access the library. Our society prioritizes car-based travel, and communities – including Topeka, Kansas – created or settled for public transit systems that include transportation deserts. Transportation barriers are barriers to full community participation. The stories shared by group interviewees illuminated the complex interconnectedness and continuing echoes of governmental policy, social and internalized expectations, and the prioritization of some residents at the expense of others in city planning and social infrastructure development and decision-making.
Keywords: Social infrastructure; Adaptive leadership; Co-cultural communication; Community engaged research; Episodic Narrative Interview